2005
DOI: 10.1258/002367705774286439
|View full text |Cite
|
Sign up to set email alerts
|

Germfree status of mice obtained by embryo transfer in an isolator environment

Abstract: The technique of embryo transfer has been evaluated for the purpose of changing the mouse stocks to a germfree (GF) status. Our results show reproducible and quality-assured conversion of animals to those which are negative for the presence of microorganisms. Rapid and easy access to GF mice is advantageous for studies of selected microflora and their cross-talks with the host, when applying, e.g. genomic, proteomic and metabolic methodology. The study involved embryo transfer in an isolator environment, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…37 This finding raises the possibility that the presence of intrauterine commensal bacteria may have a similar role in the selection of uterine T-regulatory cells as commensal gut microbiota do for colonic T-regulatory cells. While many other factors contribute to a successful pregnancy, it is worth noting that germ-free mice raised in sterile conditions have lower rates of reproductive success after embryo transfer than conventional animals, 38 suggesting a potential role for intrauterine bacteria in successful pregnancy. This potentially critical issue is largely unexplored.…”
Section: Commentmentioning
confidence: 99%
“…37 This finding raises the possibility that the presence of intrauterine commensal bacteria may have a similar role in the selection of uterine T-regulatory cells as commensal gut microbiota do for colonic T-regulatory cells. While many other factors contribute to a successful pregnancy, it is worth noting that germ-free mice raised in sterile conditions have lower rates of reproductive success after embryo transfer than conventional animals, 38 suggesting a potential role for intrauterine bacteria in successful pregnancy. This potentially critical issue is largely unexplored.…”
Section: Commentmentioning
confidence: 99%
“…To establish the role of commensal germs in neutrophil homeostasis, we took advantage of germ‐free mice 12 . These mice are maintained in special isolators and in an environment devoid of microorganisms or viruses 52 . The peripheral blood of germ‐free mice was found to contain less than 10% of normal neutrophil levels, and plasma G‐CSF was low 12 .…”
Section: Emergency Versus Steady‐state Granulopoiesismentioning
confidence: 99%
“…Although embryo transplantation technology (Smithies, 2007) is used by some commercial suppliers and others (Inzunza et al, 2005) to quickly derive new strains of GF rodents or those that have been genetically manipulated, the primary method of deriving GF rats for noncommercial operations is through surgical intervention of pregnancy at term. Another technique has been reported whereby the gut tract has been rendered sterile through the successive use of a variety of broadspectrum antibiotics.…”
Section: A Derivation Philosophymentioning
confidence: 99%
“…In spite of the previously mentioned success using embryo transfer to obtain GF mouse lines (Inzunza et al, 2005), those researchers found the traditional cesarean delivery, the classic method of deriving axenic animals, to be preferred (Norin, 2019). Since this approach is still widely used in research institutions (Carter, 1976), academic or private, and by small and large commercial lab animal suppliers, it is described in detail below.…”
Section: A Derivation Philosophymentioning
confidence: 99%